Effect of Different Extraction Method on Total Flavonoid Contents of Sansevieria trifasciata P. Leaves Extract: Pengaruh Perbedaan Metode Ekstraksi Terhadap Kadar Flavonoid Total Ekstrak Daun Lidah Mertua (Sansevieria trifasciata P. - Septiani, Gina; Susanti, Susanti; Sucitra, Fitria (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Sanseviera leaves (Sansevieria trifasciata P.) is a plant that contains flavonoids. Flavonoid in the health sector act as antibacterial, antioxidant, anti inflammatory and anti diabetic. The extraction method will determine the amount of substance on the plant extract. The purpose of this study was to determine the effect of different extraction method on total flavonoid contents of sansevieria leaves extract. The method used is an experimental by comparing meceration and soxhletation extraction method to the total flavonoid contents of sansevieria leaves extract using UV-Vis spectrophotometric. The results showed that the total flavonoid contents of the maceration extraction method was 13.934 mgQE/g or 1.39% higher than the soxhlet extraction method of 8.117 mgQE/g or 0.81%. The results of statistical tests showed that significant value of 0.001 (p<0.05), means that there is a significant effect between the contents of total flavonoids in maceration and soxhlet extraction methods.